2013
DOI: 10.1242/jeb.074716
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiinfection, from predation to schizophrenia: can animal behaviour help us understand human behaviour?

Abstract: SummaryWe examine the role of the protozoan Toxoplasma gondii as a manipulatory parasite and question what role study of infections in its natural intermediate rodent hosts and other secondary hosts, including humans, may elucidate in terms of the epidemiology, evolution and clinical applications of infection. In particular, we focus on the potential association between T. gondii and schizophrenia. We introduce the novel term ʻT. gondii-rat manipulation-schizophrenia modelʼ and propose how future behavioural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 188 publications
(270 reference statements)
2
112
0
Order By: Relevance
“…In particular, parasites commonly use the potent monoamine neurotransmitters dopamine (DA), serotonin and octopamine with conservation in structure and function across the vast range of host taxa that parasites manipulate (Pflüger and Stevenson, 2005;Shaw et al, 2009;Helluy, 2013;Libersat and Gal, 2013;McConkey et al, 2013;Vyas, 2013;Webster et al, 2013). These monoamines are also used by hosts to regulate a wide variety of brain functions from stress to reproduction (Libersat and Pflueger, 2004;Nelson and Trainor, 2007;Øverli et al, 2007).…”
Section: Neuropharmacological Host Manipulation Monoamines and Hormonesmentioning
confidence: 99%
“…In particular, parasites commonly use the potent monoamine neurotransmitters dopamine (DA), serotonin and octopamine with conservation in structure and function across the vast range of host taxa that parasites manipulate (Pflüger and Stevenson, 2005;Shaw et al, 2009;Helluy, 2013;Libersat and Gal, 2013;McConkey et al, 2013;Vyas, 2013;Webster et al, 2013). These monoamines are also used by hosts to regulate a wide variety of brain functions from stress to reproduction (Libersat and Pflueger, 2004;Nelson and Trainor, 2007;Øverli et al, 2007).…”
Section: Neuropharmacological Host Manipulation Monoamines and Hormonesmentioning
confidence: 99%
“…T. gondii can persist in brain and muscle throughout the host's life, and chronic infection is asymptomatic in immunocompetent humans (2). However, recent studies have suggested that T. gondii infection is a risk factor for developing mental diseases, such as schizophrenia and depression, as well as human behavior and personality changes and suicide (3,4). Interestingly, T. gondii infection increases the risk of schizophrenia roughly 2.7 times, which is higher than that for genes associated with schizophrenia (5).…”
mentioning
confidence: 99%
“…Characteristics of the infection also play a role, including its source (oocysts or tissue cysts), possible interactions with other infectious agents, and the genotype; thus, genotypes II and III more frequently establish chronic infections and show a greater expression of tyrosine hydroxylase genes in comparison with genotype I, and they may be more strongly related to behavioral changes [205].…”
Section: Is There An Etiological Association Between Toxoplasma Gondimentioning
confidence: 99%